Continuous, transcutaneous carbon-dioxide monitoring to avoid hypercapnia in complex catheter ablations under conscious sedation. (25th November 2020) - Weinmann, K; Lenz, A; Heudorfer, R; Aktolga, D; Rattka, M; Bothner, C; Pott, A; Oechsner, W; Rottbauer, W; Dahme, T
Abstract: Background: Ablation of complex cardiac arrhythmias requires an immobilized patient. For a successful and safe intervention and for patient comfort, this can be achieved by conscious sedation. Administered sedatives and analgesics have respiratory depressant side effects and require close monitoring. Purpose: We investigated the feasibility and accuracy of an additional, continuous transcutaneous carbon-dioxide partial pressure (tpCO2) measurement during conscious sedation in complex electrophysiological catheter ablation procedures. Methods: We evaluated the accuracy and additional value of tpCO2 detection by application of a Severinghaus electrode in comparison to arterial and venous blood gas analyses. Results: We included 110 patients in this prospective observational study. Arterial pCO2 (paCO2) and tpCO2 showed good correlation throughout the procedures (r=0.60–0.87, p<0.005). Venous pCO2 (pvCO2) were also well correlated to transcutaneous values (r=0.65–0.85, p<0.0001). Analyses of the difference of pvCO2 and tpCO2 measurements showed a tolerance within <10mmHg in up to 96–98% of patients. Hypercapnia (pCO2<70mmHg) was detected more likely and earlier by continuous tpCO2 monitoring compared to half-hourly pvCO2 measurements. Conclusion: Continuous tpCO2 monitoring is feasible and precise with good correlation to arterial and venous blood gas carbon-dioxide analysis during complex catheter ablations under conscious sedation and may contribute to additional safety. Funding Acknowledgement: Type of funding source: None